INTERAKSI KOMUNIKASI GENERASI MILENIAL, Y, DAN Z TERHADAP ORANG TUA MENURUT PERSPEKTIF ISLAM - Suryati, Muzaiyanah, Nazarmanto (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2022)
The interaction of Islamic communication was that its prevalence always adjusted to the era of the scene. Millennials, Y generations, and Z generations are the ones whose birth and growth go hand in hand with the growth of technology. This makes it impossible for those born in this generation to avoid using the Internet in everyday life. The multigenerational communication interactions of generations through the Z generation of parents have also undergone changes as compared with previous generations. In this generation, humans are progressing in their ability to use the Internet rapidly and to have an impact on daily qualities and behavior. The hallmark of this generation is innovative and creative thinking, the ability to collaborate, to create a healthy work environment to have confidence in social skills. Hence, parents must also follow and adapt to the patterns of communication interactions made by current generations. There are at least two possible communication interactions with both motivational and digital approaches.